2009
DOI: 10.1136/sti.2008.034249
|View full text |Cite
|
Sign up to set email alerts
|

Trends in marriage and time spent single in sub-Saharan Africa: a comparative analysis of six population-based cohort studies and nine Demographic and Health Surveys

Abstract: Objectives: To describe trends in age at first sex (AFS), age at first marriage (AFM) and time spent single between events and to compare age-specific trends in marital status in six cohort studies. Methods: Cohort data from Uganda, Tanzania, South Africa, Zimbabwe and Malawi and Demographic and Health Survey (DHS) data from Uganda, Tanzania and Zimbabwe were analysed. Life table methods were used to calculate median AFS, AFM and time spent single. In each study, two surveys were chosen to compare marital stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
64
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 32 publications
8
64
1
Order By: Relevance
“…In much of Southern Africa where age of first marriage is delayed, an even smaller proportion of people are in stable partnerships than in Eastern Africa. 6,7 Moreover, viral sequencing showed that 29% of new infections in the previously negative partner in a discordant relationship, came from a partner outside the primary relationship. 8 Thus, in addition to the question of the efficacy of a CVCT intervention with couples, universal VCT targeted on HIV-discordant couples is unlikely to have a major impact on the epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…In much of Southern Africa where age of first marriage is delayed, an even smaller proportion of people are in stable partnerships than in Eastern Africa. 6,7 Moreover, viral sequencing showed that 29% of new infections in the previously negative partner in a discordant relationship, came from a partner outside the primary relationship. 8 Thus, in addition to the question of the efficacy of a CVCT intervention with couples, universal VCT targeted on HIV-discordant couples is unlikely to have a major impact on the epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…This trend is also present in sub-Saharan Africa, albeit at varying levels (Bongaarts, 2007) with teenage premarital sexual activity becoming a common phenomenon in many countries (Marston et al, 2009). The research literature identifies several factors behind the trend towards increased first sex outside of marriage and delayed marriage.…”
Section: Introductionmentioning
confidence: 96%
“…Worldwide, there has been a general trend of declining age at first sex and an increasing age at first marriage (Marston et al, 2009, Harwood-Lejeune, 2001, Kirk and Pillet, 1998, Morgan SP, 2003, Wilson, 2001, Demeny and McNicoll, 2006, Mensh BS et al, 2005). This trend is also present in sub-Saharan Africa, albeit at varying levels (Bongaarts, 2007) with teenage premarital sexual activity becoming a common phenomenon in many countries (Marston et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Reports indicate that young women initiate sexual activity at an earlier age compared with boys due to factors such as cultural norms, peer pressure and economic pressure [14,15] or a combination thereof. In Ethiopia, only few studies have documented the sexual behavior of rural girls.…”
Section: Introductionmentioning
confidence: 97%